Billy Budd or about the existence of Natural Law (Prudentia Iuris, 2018)
This is the Spanish version of the class Professor Gabriel Maino (UCA-UBA) gave at Ave Maria Law School (USA). The class was about Natural Law and was attended by the students of Jurisprudence of Prof. Brian Scarnecchia. The previous reading for the assistants was a text of fiction whose drama served to illuminate the problem to approach: Billy Budd sailor, by Herman Melville. The class addressed several topics of the Natural Law theory, such us the modern concept of Law, the human nature, and the practical reason
Keywords: Natural Law; Human nature; Concept of Law; Freedom; Law and literature.